2006
DOI: 10.1093/nar/gkj442
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions of HIV-1 nucleocapsid protein with oligonucleotides

Abstract: The HIV-1 nucleocapsid (NC) protein is a small, basic protein containing two retroviral zinc fingers. It is a highly active nucleic acid chaperone; because of this activity, it plays a crucial role in virus replication as a cofactor during reverse transcription, and is probably important in other steps of the replication cycle as well. We previously reported that NC binds with high-affinity to the repeating sequence d(TG)n. We have now analyzed the interaction between NC and d(TG)4 in considerable detail, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 42 publications
(55 reference statements)
12
82
0
Order By: Relevance
“…Binding of Gag to RNA is presumably mediated by the nucleocapsid (NC) domain, with a major contribution from the two zinc fingers within this domain (9,14). Therefore, we assessed the role of RNA-binding in assembly in vivo using mutants in which zinccoordinating cysteines were replaced with serines or in which the entire NC domain was deleted.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of Gag to RNA is presumably mediated by the nucleocapsid (NC) domain, with a major contribution from the two zinc fingers within this domain (9,14). Therefore, we assessed the role of RNA-binding in assembly in vivo using mutants in which zinccoordinating cysteines were replaced with serines or in which the entire NC domain was deleted.…”
Section: Resultsmentioning
confidence: 99%
“…1) that are critical for RNA-binding specificity, nucleic acid chaperone activity Darlix et al 2011), and gRNA packaging (Gorelick et al 1999b;Kafaie et al 2008). Investigations into the RNAbinding specificity of Gag have previously studied the binding of the NC protein to RNA and DNA (Dannull et al 1994;Fisher et al 1998Fisher et al , 2006Vuilleumier et al 1999;Avilov et al 2009;Athavale et al 2010), and more recently the binding of Gag to short oligonucleotides has also been investigated (Stephen et al 2007;Wu et al 2010;Jones et al 2011). In this study, we investigate the binding of Gag and NC to longer ∼100-nt RNAs derived from the gRNA 5 ′ UTR.…”
Section: Thementioning
confidence: 99%
“…Previous studies have shown that NC binds RNAs in a largely nonspecific manner via electrostatic interactions between the nucleic acid backbone and the basic residues in the protein (Levin et al 2005;Fisher et al 2006;Vo et al 2009a;Darlix et al 2011;Wu et al 2012). However, binding to certain RNA motifs, especially single-stranded UG sequences (Fisher et al 1998), or exposed G residues in loop regions such as SL3 (De Guzman et al 1998), involves high-affinity binding in which the zinc finger (ZF) aromatic residues stack with the G base in a hydrophobic pocket formed between the two ZFs (De Guzman et al 1998;Darlix et al 2011).…”
Section: The Zinc Fingers In Gag Are Required For High-affinity Psi Rmentioning
confidence: 99%
“…70 RNA constructs lacking salient structural motifs were used to unambiguously identify binding sites located in single-stranded regions of the two conformers (Scheme 1), in agreement with the preference of NC for unpaired nucleotides. [71][72][73][74] This work demonstrated that specific interactions with the apical loop or the stem-bulge motif can have contrasting effects on RNA dimerization. In fact, loop binding was shown to hamper the palindrome's participation in intermolecular basepairing, in direct competition with the initial step of RNA dimerization.…”
Section: Introductionmentioning
confidence: 97%